EURAMED's vision on medical radiation protection (research). (October 2018) - Hoeschen, C.
While many areas of radiation protection have formed so-called 'platforms' in Europe which provide strategic research agendas for their areas of interest, this did not happen for a long while for medical exposure, which is the application of ionising radiation that causes the greatest man-made exposure, at least in first world countries. Finally, in 2015, a European medical radiation protection strategic research agenda was set up, and a corresponding platform was launched in 2016. This was named 'EURAMED' – the European Alliance for Medical Radiation Protection Research. In its strategic research agenda, EURAMED defined its vision for medical radiation protection and the corresponding research needed. Five major topics were identified, ranging from measurements of medical application-related parameters such as exposures and image quality and radiation biology aspects relevant for medical applications to individual optimisation strategies, to optimal use of techniques and harmonisation of practises, and finally to justification of the use of ionising radiation in medicine, all based on sufficient infrastructures for quality assurance. The ultimate goal is to reduce radiation exposure and risk individually for patients and staff by interdisciplinary research between clinicians, physicists, and engineers. Therefore, it is essential that the results are translated into clinical practice.